Anteromedial Labral Tears: Surgical Prevalence and Relationship with Chondral Damage of the Hip - Dwyer, Maureen; Lee, Jo Ann; McCarthy, Joseph C. (The Journal of Hip Surgery, 2019)
Structural abnormalities of the hip joint have been identified as a common cause of labral and chondral lesions of the hip joint. However, labral and chondral damage can occur in the absence of structural abnormalities. The authors examined the incidence of anteromedial (AM) labral lesions, occurring in a nonimpinging region of the hip joint, and determined if the prevalence and location of concomitant chondral lesions differ between patients with AM lesions and those without. Between 2001 and 2013, they assessed 2,080 hips (1,818 patients) undergoing hip arthroscopy for the presence of AM labral lesions (between 4 and 6 o'clock position) and documented incidence of these lesions. The articular cartilage of the posterior, superior, and anterior regions of the acetabulum and femoral head was assessed. The degree of damage was classified as absent, mild (grades I/II), or severe (grades III/IV). The prevalence and severity of lesions in each region were compared between patients with AM lesions and those without. The authors identified 1,140 hips (1,028 patients) (55%) with labral tears in the AM region of the acetabulum. The cohort consisted of 689 females and 328 males, with an average age of 37.9 ± 12 years. Chondral lesions were present in all regions of the femoral head and acetabulum in both patients with AM lesions and those without. There is a relationship between the presence of AM lesion and prevalence of chondral lesions in the posterior and anterior femoral head and acetabulum, with a higher prevalence of lesions observed in patients without AM tears. Their findings show that lesions in the AM region of the acetabular labrum can occur with high prevalence in patients. These lesions are often associated with concomitant injuries to the anterior chondral surfaces, which may differ from lesions in the impingement zone. A thorough evaluation of all regions of the hip joint is warranted during arthroscopy to identify and treat all potential lesions.
Keywords: acetabular labrum; hip arthroscopy; anteromedial